(untitled) (Applied Biological Research, 2023)
An efficient in vitro plant regeneration protocol using leaf, node and shoot tip has been developed in Corynandra felina (L. f.) Cochrane & Iltis., an endemic medicinal herb in peninsular India. The above explants, taken from field-grown plants, were sterilized, and then cultured on Murashige and Skoog’s (MS) medium supplemented with various concentrations of 6-benzylaminopurine (BAP, 0.5-3.0 mg L-1), thidiazuron (TDZ, 0.25-1.25 mg L-1) and kinetin (Kn, 0.5-3.0 mg L-1) either alone or in combination with indole-3-acetic acid (IAA, 0.25-1.0 mg L-1). Maximum number of shoots (48.3 ± 0.59) with average shoot length of 1.4 ± 0.57 cm were regenerated directly from the leaf explants grown on MS medium supplemented with TDZ (0.5 mg L-1) + IAA (0.25 mg L-1). Maximum number of shoots (5.4 ± 0.38 and 6.2 ± 0.43) with shoolength (1.9 ± 0.66 and 2.2 ± 0.19 cm) were observed in node and shoot tip explants, respectively, when cultured on MS medium supplemented with TDZ (0.5 mg L-1) + IAA (0.25 mg L-1). Tiny shoots from leaf, node and shoot tip explants were elongated (5.6 ± 0.40) on MS medium enriched with 1.0 mg L-1 GA3. The elongated shoots were rooted (90%) on half-strength MS medium fortified with 1.0 mg L-1 IBA. The regenerated plantlets when transferred to the field showed 89% plant survival. For the first time, we report direct plantlet regeneration in Corynandra felina using leaf explants.